Negative Effects of Corruption Offenses for the Country's Economy - Корнієнко, Максим Вікторович; Корнієнко, М. В.; Корниенко, Максим Викторович; Korniienko, Maksym V.; Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Єна, Ірина Вікторівна; Єна, І. В.; Ена, Ирина Викторовна; et al. (IAEME Publication, 2020)
The basic notions of "corruption" and "corruption offense" and their relationship are considered. Statistical data concerning the Corruption Perceptions Index in 166 countries is analyzed. Its relationship with the development of the economic sector is also taken into consideration. The main consequences of corruption offenses for the country's economy are determined. Cause-effect relationships have been identified between the Corruption Perceptions Index, GDP per capita and the Human Development Index (HDI) based on panel data from 166 countries in 2018. Human capital and poverty are prerequisites for corruption, which is a significant contribution to the scientific literature on the preconditions and causes of corruption offenses. The impact of corruption offenses on the country’s economy at the macro and micro levels is considered. It is еstablished that it is necessary to ensure the development of human capital, political stability, institutional independence, the development of partnership between the state and society in order to minimize corruption offenses.

Розглянуто основні поняття "корупція" та "корупційне правопорушення", а також їх взаємозв'язок. Проаналізовано статистичні дані щодо індексу сприйняття корупції у 166 країнах. Також враховується його взаємозв'язок з розвитком економічного сектору. Визначено основні наслідки корупційних правопорушень для економіки країни. Причинно-наслідкові зв’язки були виявлені між індексом сприйняття корупції, ВВП на душу населення та індексом людського розвитку (ІЛР) на основі лонгитюдних даних 166 країн у 2018 р. Людський капітал та бідність є передумовою корупції, що зазначено у науковій літературі про передумови та причини корупційних правопорушень. Розглядається вплив корупційних правопорушень на економіку країни на макро- та мікрорівні. Встановлено, що необхідно забезпечити розвиток людського капіталу, політичну стабільність, інституційну незалежність, розвиток партнерства між державою та суспільством, щоб мінімізувати корупційні правопорушення.

Рассмотрены основные понятия "коррупция" и "коррупционное правонарушение", а также их взаимосвязь. Проанализированы статистические данные по индексу восприятия коррупции в 166 странах. Также учитывается его взаимосвязь с развитием экономического сектора. Определены основные последствия коррупционных правонарушений для экономики страны. Причинно-следственные связи были обнаружены между индексом восприятия коррупции, ВВП на душу населения и индексом человеческого развития (ИЧР) на основе лонгитюдных данных 166 стран в 2018 году. Человеческий капитал и бедность является предпосылкой коррупции, о чем говорится в научной литературе о предпосылках и причинах коррупционных правонарушений. Рассматривается влияние коррупционных правонарушений на экономику страны на макро- и микроуровне. Установлено, что необходимо обеспечить развитие человеческого капитала, политическую стабильность, институциональную независимость, развитие партнерства между государством и обществом, чтобы минимизировать коррупционные правонарушения.
Korniienko M. V. Negative Effects of Corruption Offenses for the Country's Economy / M. V. Korniienko, I. V. Petrunenko, I. V. Yena, K. O. Pankratova, K. A. Vozniakovska // International Journal of Management. – V. 11 (5). – IAEME Publication, 2020. – P. 1072-1083.
Keywords: Corruption offense; Corruption; Economy; Economic growth; Consequences of corruption; корупційне правопорушення; корупція; економіка; економічне зростання; наслідки корупції; коррупционное правонарушение; коррупция; экономика; экономический рост; последствия коррупции; Research Subject Categories::LAW/JURISPRUDENCE